EXPLORING SMART CITY CHARACTERISTICS FOR “TOURISM-FOR-ALL” INITIATIVES IN URBAN DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - Hassnah WEE; Mohd Saufi ANAS; Alfian THOMAS (Geo Journal of Tourism and Geosites, 2023)
The study presents a systematic literature review conducted following a rigorous search protocol that identified 7900 articles published in SCOPUS-indexed journals in 2001-2021. These articles were filtered using the PRISMA approach, resulting in the selection of 61 relevant papers. The research outcome offers essential insights into the core characteristics of smart cities in urban development, encompassing five primary dimensions: government, citizens, technology, mobility, and the environment, over the past two decades. The findings of this study benefit smart city stakeholders, recommends using the “Tourism-For-All” destination concept in urban development, and contributes to the emerging “Purple Tourism” framework.